The Readiness of Thai Accounting Students for the ASEAN Economic Community: An Exploratory Study - Suttipun, Muttanachai (Asian Journal of Business and Accounting, 2014)
The ASEAN Economic Community (AEC) will be established in 2015 to integrate the regional economy. A professional accountant in a member country may then apply to practice in other member countries. This exploratory study investigates the competencies of Thai accounting students and their readiness for the AEC, and also tests for the relationships between the students’ competencies and their level of readiness. This study finds that the accounting students’ Ethical, Knowledge, Capability, and Relationship competencies are at the high level, while their Analysis competency is only at the moderate level. The level of students’ readiness for the AEC is indicated to be at the medium high level. The results of the regression analysis show a significant positive relationship between the accounting students’ Capability, Knowledge, Ethical and Relationship competencies, and the level of their readiness for the AEC. Keywords: Accounting Students, ASEAN Economic Community, Thailand JEL Classification: M49